Monitoring and therapeutics of joint pain in dogs - Calin I. HULEA; Romeo Teodor CRISTINA (Medicamentul Veterinar)
Osteoarthritis in the dog is one of the most common musculoskeletal disorders that has become a medical and financial problem for the owners. A big problem is treating of the dogs suffering from the side effects that arise as a consequence of OA pain therapy. In the present study, 19 dogs of different races with definite diagnoses of osteoarthritis (OA) and / or hip dysplasia (DSC) were included. In pursuit of the condition of healing / amelioration of osteoarthritis conditions in dogs, two objectives were followed: a) the chronic pain monitoring of acupuncture dogs, via a well-established questionnaire, a multifactorial descriptive scale; b) Influence of acupuncture on blood parameters in chronic pain in the dogs. Dogs grouping was based on the previous use of analgesics and on the Helsinki Chronic Pain Index (HCPI). The dogs were randomly divided into two lots: a group that received acupuncture and antalgic treatments and a placebo (control) not treated. Initially the animals in the study were subjected to exploratory radiographs, and blood samples were collected to determine prolactin and serotonin values. The results revealed that both serotonin and prolactin did not undergo significant quantitative changes during the study in both dogs groups, receiving acupuncture and those in the control group. The questionnaire used is a valid tool for assessing chronic locomotor pain in dogs and we recommend it for the clinical trials.